The State of the Welfare State: Unemployment, Labor Market Policy, and Inequality in the Age of Workfare - Rueda, D (City University of New York, 2015)
This paper argues that since the 1990s the welfare state has been transformed into a workfare state. It proposes a stylized framework to understand the influence of unemployment on inequality and the effects of labor market policy. Using this framework, the paper shows that the transformation of the welfare state has made the effects of unemployment more inegalitarian. I analyze OECD data on inequality and redistribution from the mid-1970s to the late 2000s and provide preliminary but systematic regression results. They suggest that the generosity of labor market policy promoted higher levels of market income equality only during the traditional welfare period. They also suggest that the responsiveness of redistribution to unemployment has become weaker in the era of workfare.